PENGARUH MANAJEMEN RANTAI PASOK BERBASIS SISTEM ERP DALAM MENINGKATKAN KINERJA PT POS INDONESIA - Olivia Lysion; Metta Noviani; Cindy Cindy; Yen Diarti; Jacky Gunadi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Many companies have implemented supply chain value integration systems such as ERP. One of them is PT Pos Indonesia which implements an ERP system in order to integrate activities into a system. ERP has elements and components that can be integrated into activities such as HRM, R&D, marketing and finance. Other advantages of implementing ERP are knowing sales predictions, managing inventory, being able to control all activities in one system. Recommendations for future research to test the ERP system for improving performance at the PT Pos Indonesia company.